2007
DOI: 10.1577/t06-078.1
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Estimates of Natural Mortality for Chesapeake Bay Blue Crab

Abstract: Abstract.-Analyses of the population dynamics of blue crab Callinectes sapidus have been complicated by a lack of estimates of the instantaneous natural mortality rate (M). We developed the first direct estimates of M for this species by solving Baranov's catch equation for M given estimates of annual survival rate and exploitation rate. Annual survival rates were estimated from a tagging study on adult female blue crabs in Chesapeake Bay, and female-specific exploitation rates for the same stock were estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 50 publications
1
45
0
Order By: Relevance
“…This ap proach is rather generic and can probably be applied to other crustacean populations that have a terminal molt, insofar as they are seasonally breeding, univoltine (or perhaps even bivoltine), and ex hibit interannual variability of adult body size and numbers. The natural mortality estimate we obtained (0.66 yr −1 ) was high but similar to estimates of 0.53 to 1.02 yr −1 for sublegal (< 95 mm CW) adult male snow crabs in the southern Gulf of St. Lawrence (Wade et al 2003) and less than estimates reported for adult females of other crab species with a terminal molt (Miller et al 2005, Zheng 2005, Hewitt et al 2007). For snow crabs specifically, natural mortality of adult females was estimated at 0.56 yr −1 in 2 distinct studies: one performed in a small (13.7 km marine re serve in the Sea of Japan using tag-recapture methods (Yamasaki et al 2001) and the other at the scale of the eastern Bering Sea using numerical ac counting (Zheng 2003).…”
Section: Discussionsupporting
confidence: 84%
“…This ap proach is rather generic and can probably be applied to other crustacean populations that have a terminal molt, insofar as they are seasonally breeding, univoltine (or perhaps even bivoltine), and ex hibit interannual variability of adult body size and numbers. The natural mortality estimate we obtained (0.66 yr −1 ) was high but similar to estimates of 0.53 to 1.02 yr −1 for sublegal (< 95 mm CW) adult male snow crabs in the southern Gulf of St. Lawrence (Wade et al 2003) and less than estimates reported for adult females of other crab species with a terminal molt (Miller et al 2005, Zheng 2005, Hewitt et al 2007). For snow crabs specifically, natural mortality of adult females was estimated at 0.56 yr −1 in 2 distinct studies: one performed in a small (13.7 km marine re serve in the Sea of Japan using tag-recapture methods (Yamasaki et al 2001) and the other at the scale of the eastern Bering Sea using numerical ac counting (Zheng 2003).…”
Section: Discussionsupporting
confidence: 84%
“…maximum size), and the potential vulnerability under different levels of exploitation (Frisk et al, 2001). Nevertheless, accuracy of such empirical methods depends on the variability among the species for which the empirical relationship has been constructed and how well the demographic traits have been estimated for the stock of interest (Hewitt et al, 2007). Other option is to use unstructured model of biomass dynamic, but these kind of model do not allow the incorporation of age-related processes affecting population functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hewitt et al (2007) estimated an annual instantaneous rate of natural mortality for blue crab in Chesapeake Bay as M=0.9. This value is an expected value based on both observed and theoretical considerations.…”
Section: Discussionmentioning
confidence: 99%